Development of a chemical-free process utilizing ozone oxidative precipitation for the recovery of cobalt and manganese from acid mine drainage. Issue 5 (October 2022) - Shekarian, Younes; Hassas, Behzad Vaziri; Rezaee, Mohammad; Pisupati, Sarma V.
Abstract: Acid mine drainage (AMD) has been identified as a viable secondary resource of Co, and Mn. However, recovery of these elements while treating AMD is challenging due to the unfavorable pH and Eh conditions for Co-Mn precipitation. This study investigated the effects of various ligands (hydroxide, carbonate, ammonium, sulfate, and phosphate) and oxidizers (sodium persulfate, potassium permanganate, and ozone) on the precipitation of Co-Mn from AMD through experimental and solution chemistry studies. Ozone was found to be the most effective agent for the recovery of these elements. Based on the results, an AMD treatment process was formulated for selective recovery of multiple critical elements, including Al, REEs, Co, and Mn. More than 95 % of Co and Mn were recovered through the proposed process utilizing chemical-less ozone oxidative precipitation. A precipitate containing 0.9 % Co and 54.6 % Mn was obtained from an AMD source containing 0.9 ppm Co and 41.8 ppm Mn. Highlights: Precipitation of Co and Mn from AMD was studied using various ligands and oxidizers. The highest recovery and grade of Co and Mn were obtained using ozone oxidative precipitation. Using this process, more than 95 % of Co and Mn were recovered from AMD. A product containing 54.6 % Mn and 0.9 % Co was obtained. Modification of AMD treatment process for recovering multiple critical elements was formulated.